Customer Satisfaction of Cellular Phone Services In Kottayam District - Dr.E. Muthukumar; R. Bhuvaneswari; M.Sathiskumar (Journal of Exclusive Management Science, 2015)
After the liberalization of the Indian Telecom Sector, 1994, the Indian cellular market witnessed a higher growth in cellular services. By 2005, there were a total of 12 players in the market with the five major players being Bharati Televentures Limited (Bharati). Bharat Sanchar Nigam Limited (BSNL), Hutchinson-Eassar Limited (Hutch), Idea Cellular Limited (Idea) and Reliance Indian Mobile (RIM). All the players except RIM offered services based on the Global system for mobile (GSM) technology. RIM provided services based on Code Division Multiple Access (CDMA) technology as well as GSM. As competition in the telecom area intensified, service providers took new initiatives to customers. Prominent among these were celebrity, endorsements, loyalty rewards, discount coupons, business solutions and talk time services. The most important consumer segments in the Cellular industry were the youth segment and the business class segment. The youth segment was the largest and fastest growing segment and was therefore targeted by cellular service providers. Hence all the service providers concentrate on more service quality to attract new customers in GSM market.